A depth-encoding PET detector that uses light sharing and single-ended readout with silicon photomultipliers. (13th February 2018) - Kuang, Zhonghua; Yang, Qian; Wang, Xiaohui; Fu, Xin; Ren, Ning; Sang, Ziru; Wu, San; Zheng, Yunfei; Zhang, Xianming; Hu, Zhanli; Du, Junwei; Liang, Dong; et al.
Abstract: Detectors with depth-encoding capability and good timing resolution are required to develop high-performance whole-body or total-body PET scanners. In this work, depth-encoding PET detectors that use light sharing between two discrete crystals and single-ended readout with silicon photomultipliers (SiPMs) were manufactured and evaluated. The detectors consisted of two unpolished 3 × 3 × 20 mm 3 LYSO crystals with different coupling materials between them and were read out by Hamamatsu 3 × 3 mm 2 SiPMs with one-to-one coupling. The ratio of the energy of one SiPM to the total energy of two SiPMs was used to measure the depth of interaction (DOI). Detectors with different coupling materials in-between the crystals were measured in the singles mode in an effort to obtain detectors that can provide good DOI resolution. The DOI resolution and energy resolution of three types of detector were measured and the timing resolution was measured for the detector with the best DOI and energy resolution. The optimum detector, with 5 mm optical glue, a 9 mm triangular ESR and a 6 mm rectangular ESR in-between the unpolished crystals, provides a DOI resolution of 2.65 mm, an energy resolution of 10.0% and a timing resolution of 427 ps for events of E > 400 keV. The detectors simultaneously provide good DOI and timing resolution, and show great promise for the development of high-performance whole-body and total-body PET scanners.